2019
DOI: 10.1080/14397595.2019.1630897
|View full text |Cite
|
Sign up to set email alerts
|

Organ system improvements in Japanese patients with systemic lupus erythematosus treated with belimumab: A subgroup analysis from a phase 3 randomized placebo-controlled trial

Abstract: Roth (2020) Organ system improvements in Japanese patients with systemic lupus erythematosus treated with belimumab: A subgroup analysis from a phase 3 randomized placebo-controlled trial,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…[17][18][19][20] The efficacy and safety of belimumab in patients with SLE were examined in previous phase III trials, which demonstrated that belimumab-treated patients have reductions in disease activity, new organ damage accrual and corticosteroid dose. [21][22][23][24] Long-term continuation studies involving 7-13 years of belimumab treatment have confirmed that efficacy and acceptable safety and tolerability profile were maintained over this time. [25][26][27] However, limited data exist on the long-term efficacy and safety of belimumab in patients with SLE from Japan and South Korea.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 90%
“…[17][18][19][20] The efficacy and safety of belimumab in patients with SLE were examined in previous phase III trials, which demonstrated that belimumab-treated patients have reductions in disease activity, new organ damage accrual and corticosteroid dose. [21][22][23][24] Long-term continuation studies involving 7-13 years of belimumab treatment have confirmed that efficacy and acceptable safety and tolerability profile were maintained over this time. [25][26][27] However, limited data exist on the long-term efficacy and safety of belimumab in patients with SLE from Japan and South Korea.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 90%
“…There were 3 reports of Phase II clinical trials, each using a different efficacy index. Two reports by Tanaka et al 30 , 31 were a subgroup analysis of data from only Japanese subjects only recruited in the multi-national BLISS-NEA study, and many indexes were reported. These reports were analyzed after confirming no overlapping of results.…”
Section: Resultsmentioning
confidence: 99%
“…24 The analysis of SLEDAI scores showed a significant improvement in the musculoskeletal, renal and immunological items, a decrease in serum anti-dsDNA antibody titre, an increase in complement activity and a reduction in glucocorticoid dose in the belimumab group compared with the placebo group. 25 The BLISS-SC (ClinicalTrials.gov Identifier: NCT01484496) study investigated 836 patients with SLE and a SLEDAI score of ≥8, and reported that the proportion of patients achieving SRI-4 response at 52 weeks was significantly higher in the belimumab group (200 mg subcutaneous injection once weekly) than in the placebo group (61% versus 48%). 26 The safety profile was unremarkable.…”
Section: Belimumab Therapy In Systemic Lupus Erythematosusmentioning
confidence: 99%